Shock city image and architecture in industrial Manchester - Crinson, Mark 1959- (Paul Mellon Centre for Studies in British Art, 2022)
From the mid-eighteenth century to the nineteen-twenties, from the birth of the Industrial Revolution to the height of Manchester's global significance and the beginning of its decline, Shock City challenges the idea that Paris was the "capital of the nineteenth century." Mark Crinson reorients this issue around the development of industrial production, particularly cotton and its manufacture by means of steam power, offering a fascinating and accessibly written account of how new relations in the industrial economy were manifested through the spaces and representations of the first industrial city.0Focusing on Manchester's mills and warehouses, its main trading institution (the Royal Exchange), its magnificent Gothic Revival Town Hall, and its late Gothic Revival Rylands Library, this book explores these iconic buildings alongside paintings, prints, maps, and photographs of the city throughout the period. Crinson interweaves analysis of buildings and images, urban spaces and new institutions, technology and industrial pollution to show how these were all the products of Manchester's newly emergent industrial middle classes, who remade the city in their image.
Keywords: Geschichte 1800-1900; Kultur; Architektur; Manchester; Industries / England / Manchester / History / 18th century; Industries / England / Manchester / History / 19th century; Industries / England / Manchester / History / Pictorial works; Industrial buildings / England / Manchester / History / 18th century / Pictorial works; Industrial buildings / England / Manchester / History / 19th century / Pictorial works; Manchester (England) / Economic conditions / 18th century; Manchester (England) / Economic conditions / 19th century; Manchester (England) / Buildings, structures, etc / Pictorial works; Buildings; Economic history; Industrial buildings; Industries; England / Manchester; 1700-1899; History; Pictorial works